2019
DOI: 10.1016/j.jpeds.2018.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Social Risk Factors Impact Hospital Readmission and Outpatient Appointment Adherence for Children with Congenital Heart Disease

Abstract: Objective: To examine the relations of individual and cumulative social risk factors to hospitalization outcomes and adherence to outpatient cardiology appointments within the first two years of life for congenital heart disease (CHD) survivors.Study design: Data were extracted for 219 patients who underwent infant cardiac surgery with cardiopulmonary bypass. Cumulative social risk was dichotomized into high social risk (≥2 risk factors; N=103) versus low social risk (≤1 risk factor; N=116). Risk of morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Our study is among the surveys with the largest sample sizes in clinical BD research. Although most of our findings can be supported by previous studies, these well-known studies in BDs include no more than 1000 cases, even in developing countries [ 10 , 11 ]. For example, Down syndrome is the most common BD group and a significant contributor to neonatal and infant death.…”
Section: Discussionsupporting
confidence: 83%
“…Our study is among the surveys with the largest sample sizes in clinical BD research. Although most of our findings can be supported by previous studies, these well-known studies in BDs include no more than 1000 cases, even in developing countries [ 10 , 11 ]. For example, Down syndrome is the most common BD group and a significant contributor to neonatal and infant death.…”
Section: Discussionsupporting
confidence: 83%
“…Greater representation of racial, ethnic and socioeconomic diversity is particularly important, given the influence of these factors on physical and mental health service use. 8,88…”
Section: Limitations Of Captured Studies and The Current Reviewmentioning
confidence: 99%
“…[29][30][31][32][33] Specifically, this body of work has frequently examined area-level measures of social determinants of health (e.g., area deprivation index, census tract, ZIP code, and county-level factors), and the specific subset of studies that do examine the effect of social needs at the individual level often rely on data extracted from notes rather than from formal diagnostic codes. 29,[31][32][33][34][35][36][37][38][39][40][41] To more precisely estimate the effect of SDOH or HRSN, the statistical models used in this body of work often control for a common set of covariates including sex, race, age, marital status, comorbidities, social determinants of health or social risk, and hospital or site characteristics. 29,30,[34][35][36][37]42,43 The effect of SDOH or HRSN has varied, but studies have identified that 34% of patients with two HRSN and 24.5% of patients with housing instability have hospital readmission, and for those who live in areas of high deprivation, the odds ratio of readmission was 1.7.…”
Section: Introductionmentioning
confidence: 99%